2005
DOI: 10.1385/mb:31:2:151
|View full text |Cite
|
Sign up to set email alerts
|

The ERK Cascade: A Prototype of MAPK Signaling

Abstract: Sequential activation of protein kinases within the mitogen-activated protein kinase (MAPK) cascades is a common mechanism of signal transduction in many cellular processes. Four such cascades have been elucidated thus far, and named according to their MAPK tier component as the ERK1/2, JNK, p38MAPK, and ERK5 cascades. These cascades cooperate in transmitting various extracellular signals, and thus control cellular processes such as proliferation, differentiation, development, stress response, and apoptosis. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
302
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 400 publications
(308 citation statements)
references
References 251 publications
5
302
0
1
Order By: Relevance
“…Fourteen MAPK isoforms have been identified in mammalian cells, which can broadly be divided into four groups, the classical MAPK (ERK1 and ERK2), p38 MAPK, JNK and atypical MAPK, which include ERK5, ERK3 and ERK8 [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Fourteen MAPK isoforms have been identified in mammalian cells, which can broadly be divided into four groups, the classical MAPK (ERK1 and ERK2), p38 MAPK, JNK and atypical MAPK, which include ERK5, ERK3 and ERK8 [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we investigated the impact of blocking the extracellular signal-regulated kinase (ERK1/2) MAPK signaling pathway on Mcl-1 protein expression. Although ERK1/2 MAPK have been frequently associated with cellular proliferation, their role in promoting survival in different cellular models became recently evident (Rubinfeld and Seger, 2005;Sridhar et al, 2005;Yoon and Seger, 2006). Phospho-ERK1/2 were previously shown to be overexpressed in LNCaP-IL-6 þ (Gioeli et al, 1999;Steiner et al, 2003) and Du145 prostate cancer cells (Shimada et al, 2002) and clinical specimens (Gioeli et al, 1999;Royuela et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…ERK including ERK1 and ERK2 belongs to the MAPKs family, and accumulating evidences suggest that ERK signal path way may take part in pathogenesis of depression and the mechanism of antidepressant-like action (Gourley et al, 2008). ERK is one of the most-studied intracellular signaling pathways and it is highly sensitive to stress and closely associated with mood processing (Gerrits et al, 2006;Rubinfeld and Seger, 2005). Moreover, recent studies have demonstrated a positive modulation of ERK1/2 by antidepressant drugs such as fluoxetine (Kuo et al, 2013).…”
Section: Discussionmentioning
confidence: 99%